Management techniques for librarians - Evans, G. Edward (New York : Academic Press, 1976)
This is concerned with basic management of all types of libraries such as planning, organizing controlling etc.
Includes bibliographical references and index.
kjo 18/01/2019
Loans
Keywords: Library administration